Epigenetic Transgenerational Actions of Vinclozolin on the Development of Disease and Cancer - Skinner, Michael K. (Crit Rev Oncog, 2007)
Exposure to an environmental endocrine disruptor (e.g., vinclozolin) during embryonic gonadal sex determination appears to alter the male germ line epigenome and subsequently promotes transgenerational adult onset disease. The epigenetic mechanism involves the induction of new imprinted-like genes/DNA sequences in the germ line that appear to transmit disease phenotypes. The disease phenotypes include testis abnormalities, prostate disease, kidney disease, immune abnormalities, and tumor development. This epigenetic transgenerational disease mechanism provides a unique perspective from which to view inheritable adult onset disease states, such as cancer, and ultimately offers new insights into novel diagnostic and therapeutic strategies.